2021
DOI: 10.21203/rs.3.rs-179897/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polystyrene microplastics induce blood-testis barrier disruption regulated by MAPK-Nrf2 signaling pathway in rats

Abstract: As a persistent organic pollutant, microplastics (MPs) have been reported to induce sperm quantity decrease in male rats. However, the related mechanism remains obscure. Therefore, this study is intended to explore the effects of polystyrene microplastics (PS-MPs) on male reproduction and its related mechanism of blood-testis barrier (BTB) impairment. Thirty-two adult male Wistar rats were divided randomly into four groups fed with PS-MPs for 90 days at the dose of 0 mg/d (control group), 0.015 mg/d, 0.15 mg/d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It also demonstrated that long-term MP exposure was a key risk factor that elicited oxidative stress in mice. MNPs could mediate the MAPK-Nrf2 signaling pathway by inducing oxidative stress, leading to the disruption of the blood-testis barrier in rats; thereby affecting the reproductive performance of rats (51). Another study found that MNPs could induce oxidative stress by activating the fibrosis-related Wnt/β-catenin signaling pathway to induce apoptosis in rat cardiomyocytes (71).…”
Section: Discussionmentioning
confidence: 99%
“…It also demonstrated that long-term MP exposure was a key risk factor that elicited oxidative stress in mice. MNPs could mediate the MAPK-Nrf2 signaling pathway by inducing oxidative stress, leading to the disruption of the blood-testis barrier in rats; thereby affecting the reproductive performance of rats (51). Another study found that MNPs could induce oxidative stress by activating the fibrosis-related Wnt/β-catenin signaling pathway to induce apoptosis in rat cardiomyocytes (71).…”
Section: Discussionmentioning
confidence: 99%
“…Several adverse reproductive effects are observed in male mammals following oral exposure to MNPs of various size and with varying duration. For example, male rodents' oral exposure to PS-MNP leads to accumulation within the testis (51)(52)(53)(54)(55), coupled to disruption of the seminiferous epithelium (51,52,54,(56)(57)(58)(59)(60), evidence of localized oxidative stress and mitochondrial dysfunction (47), and over-expression of pro-inflammatory cytokines in the testis (52,53). This same exposure is associated with disruption of the blood-testis barrier (52,58,59,61), with in vitro studies demonstrating oxidative stress, endoplasmic reticulum stress and misfolding/degradation of tight junctional proteins in Sertoli cells (62,63).…”
Section: Fertility Effects In Adult Malesmentioning
confidence: 99%
“…For example, male rodents' oral exposure to PS-MNP leads to accumulation within the testis (51)(52)(53)(54)(55), coupled to disruption of the seminiferous epithelium (51,52,54,(56)(57)(58)(59)(60), evidence of localized oxidative stress and mitochondrial dysfunction (47), and over-expression of pro-inflammatory cytokines in the testis (52,53). This same exposure is associated with disruption of the blood-testis barrier (52,58,59,61), with in vitro studies demonstrating oxidative stress, endoplasmic reticulum stress and misfolding/degradation of tight junctional proteins in Sertoli cells (62,63). There are clear functional consequences of these exposures, as MNP exposure in rodent models leads to reduced sperm quantity and quality (51-54, 57, 59, 61, 64, 65) in addition to reduced testicular androgen production (57) and circulating levels of testosterone (51,54,56,57,61) and luteinizing hormone (LH) (51,54,56,57), suggesting that MNP exposure may have important implications in the pituitarygonadotropin endocrine signalling pathways, testis function and sperm quality in male mammals [see D'Angelo and Meccariello for a review on this topic (66)].…”
Section: Fertility Effects In Adult Malesmentioning
confidence: 99%